Wychowawcze oddziaływanie obcowania z kulturą w kontekście pomocy postpenitencjarnej - Nowak, Barbara (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The paper deals with the impact of culture on convicted offenders. Culture is an important element of post-penitentiary assistance, indicating to inmates the possibility of focusing their efforts on spiritual values, with which many of them have not identified themselves before. Culture as part of the everyday life of society encompasses, among others, customs, ways of satisfying basic needs, superstitions, beliefs, broadly defined ideology, everyday life including family relations, questions of upbringing and, finally, fashion. An extremely important element of culture is the need to promote it, i.e. a planned process of its dissemination the objective of which is to make cultural goods accessible to as many people as possible.
Keywords: pomoc postpenitencjarna; kara pozbawienia wolności; skazani przestępcy